SISTEM INFORMASI PELAYANAN SURAT-SURAT AKADEMIK MENGGUNAKAN SMS GATEWAY DI FAKULTAS ILMU BUDAYA UNIVERSITAS BRAWIJAYA - Farid, Mukhammad; Widarti, Dinny Wahyu (DINAMIKA DOTCOM, 2016)
Academic division in Faculty of Culture Studies, University of Brawijaya is one of technicalservice units which serves all students in academic matters. Information system of lettersadministration in academic division in faculty of Culture Studies, University of Brawijaya webbasedby using PHP, MySQL database and application of SMS gateway Gammu and by usingSystem Development Life Cycle (SDLC) method which consists some steps, those are systemplanning, system analysis, system design, system selection, system implementation, and systemmaintenance. The result of this research is application of students academic letters validationcreated in Faculty of Culture Studies of University of BrawijayaKeywords:Informatian Systems, SMS Gateway, PHP, MySQL.